Aberrant cellular retinol binding protein 1 (CRBP1) gene expression and promoter methylation in prostate cancer. Issue 8 (27th July 2004) - Jerónimo, C; Henrique, R; Oliveira, J; Lobo, F; Pais, I; Teixeira, M R; Lopes, C
Abstract : Aims: Retinoids are involved in cell growth, differentiation, and carcinogenesis. Their effects depend on cytosolic transport and binding to nuclear receptors. CRBP1 encodes a protein involved in this process. Because altered CRBP1 expression and promoter hypermethylation occur in several tumours, these changes were investigated in prostate tumorigenesis. Methods: The CRBP1 promoter was assessed by methylation specific polymerase chain reaction on tissue samples from 36 radical prostatectomy specimens (paired normal tissue, adenocarcinoma, and high grade prostatic intraepithelial neoplasia (HGPIN)), 32 benign prostatic hyperplasias (BPHs), and 13 normal prostate tissue samples from cystoprostatectomies. Methylation of DNA extracted from microdissected tissue was examined blindly. CRBP1 expression was assessed by immunohistochemistry on formalin fixed, paraffin wax embedded tissue. Results: Loss of CRBP1 expression was seen in 15 of 36 adenocarcinomas and 18 of 36 HGPINs. Fifteen adenocarcinomas and nine HGPINs showed overexpression, whereas the remainder showed normal expression. BPH displayed normal expression. No significant associations were found between CRBP1 expression and Gleason score or stage. CRBP1 promoter hypermethylation was found in 17 of 36 adenocarcinomas, three of 35 HGPINs, one of 36 normal prostate tissues from the same patients, none of 32 BPHs, and none of 13 normal prostate tissues from cystoprostatectomies. Loss of expression and hypermethylation of CRBP1 were not significantly associated. Conclusions: Altered CRBP1 expression and hypermethylation are common in prostate carcinoma, although CRBP1 hypermethylation is not an early event in tumorigenesis. Moreover, both adenocarcinoma and HGPIN show frequent CRBP1 overexpression. The molecular mechanisms underlying altered CRBP1 expression in prostate cancer deserve further study.